2017
DOI: 10.3390/ijerph14091087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physiological and Psychological Relaxation Using Measurements of Heart Rate Variability, Prefrontal Cortex Activity, and Subjective Indexes after Completing Tasks with and without Foliage Plants

Abstract: Abstract:The objective of this study was to compare physiological and psychological relaxation by assessing heart rate variability (HRV), prefrontal cortex activity, and subjective indexes while subjects performed a task with and without foliage plants. In a crossover experimental design, 24 university students performed a task transferring pots with and without a foliage plant for 3 min. HRV and oxyhemoglobin (oxy-Hb) concentration in the prefrontal cortex were continuously measured. Immediately thereafter, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 56 publications
(75 reference statements)
7
48
0
1
Order By: Relevance
“…Previous studies have reported the effects of visual stimulation by green plants on physiological and psychological relaxation (Park et al, 2016d;Son et al, 1998). Specifically, Park et al (2017) reported that the reachinggrasping task with green plants showed a higher stabilizing effect on the autonomic nervous system such as cerebral blood flow and sympathetic nerve activity than the reaching-grasping task without a green plant. Therefore, performing functional tasks through horticultural activity can provide psychophysiological and psychological stabilization effects as well as the physical effects that are commonly obtained through the repetition of a functional task.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the effects of visual stimulation by green plants on physiological and psychological relaxation (Park et al, 2016d;Son et al, 1998). Specifically, Park et al (2017) reported that the reachinggrasping task with green plants showed a higher stabilizing effect on the autonomic nervous system such as cerebral blood flow and sympathetic nerve activity than the reaching-grasping task without a green plant. Therefore, performing functional tasks through horticultural activity can provide psychophysiological and psychological stabilization effects as well as the physical effects that are commonly obtained through the repetition of a functional task.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings have been reported in previous studies. When 24 men in their 20s performed the same tasks with and without foliage plants, the oxyhemoglobin concentration in the left prefrontal cortex of the subjects was lowered when performing the task with plants; this result suggests that tasks involving living foliage plants induce more physiological relaxation than working without foliage plants (Park et al, 2017). Furthermore, they also felt significant positive emotions, such as being more comfortable, natural, and relaxed compared with performing the task without plants (Park et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…When 24 men in their 20s performed the same tasks with and without foliage plants, the oxyhemoglobin concentration in the left prefrontal cortex of the subjects was lowered when performing the task with plants; this result suggests that tasks involving living foliage plants induce more physiological relaxation than working without foliage plants (Park et al, 2017). Furthermore, they also felt significant positive emotions, such as being more comfortable, natural, and relaxed compared with performing the task without plants (Park et al, 2017). According to Choi et al (2016), only a 5% index of indoor greenness could provide benefits in psychophysiological stability by stimulating the autonomic nervous system, such as EEG and heart rate variability, and is associated with positive feelings such as ''clean, '' ''soft,'' ''bright,'' ''warm,'' ''vibrant,'' ''comfortable,'' and ''fresh.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, working with plants has demonstrated psychophysiological effects, invoking positive emotional changes. For instance, participants who participated in activities using plants showed increased alpha-waves in the brain, stabilized brain blood flow, and heart beats [46,47]. In another study, 30 adults with intellectual disabilities who participated in horticultural activities exhibited steadiness of the autonomic nervous system and reductions in the stress hormone, cortisol [48].…”
Section: Discussionmentioning
confidence: 99%